Diagnosis of hemogobinopathies in the clinical laboratory: an occult Hofu hemoglobin on HPLC - Urroz Maitane Echeverría; Delgado Ana Isabel López; Conejero Raquel Oliveros; Nistal David Álvarez (Advances in Laboratory Medicine)
Hemoglobinopathies are disorders affecting the structure, function and/or production of hemoglobin. These conditions are caused by mutations in the genes encoding globin synthesis. The highly variable clinical manifestations of hemoglobin disorders range from asymptomatic forms to severe anemia. Laboratory tests are crucial for diagnosis.